Analisis Awal Potensi Renewable Energy di Bawah Jembatan Aur Duri II Jambi - S Umar Djufri (Universitas Batanghari Jambi, 2018)
The city of Jambi is dibentangi River batanghari, study on utilization of renewable electricity in particular an against water power through Streams need to be consider for perencanan Micro Hydro power plant (PLTMH). Water conditions that can be utilized as a resource (resources) electric generator has a capacity of flow and elevation of water channel system. The main problems in hydropower generation is the availability of water of the river discharge as energy for propulsion power plant. Therefore it takes a specific technique to predict the potential flow of river water on all the time or signature debit River that can be used for energy micro hydro power plant, not the onset of rain with a long time as well as the condition of watersheds (DAS) that can cause critical flow of river water into small even dried up. River discharge measurements manually at any given time can only represent the volume of discharge of the River at the time of measurement is performed. Changes that occur due to the onset of rain in the next time, or decrease in discharge of the River because the groundwater deposits shrink, can not be observed with either it needs to be planned debit kontiniu for turbine generator round capacity taking into account the capacity of electricity from generators that can be optimally raised